APPLICATION OF THE TALKING CHIPS MODEL TO INCREASE STUDENTS' LEARNING MOTIVATION ON THE MATERIAL OF THE PROPERTIES OF OBJECTS FOR CLASS V SDN 27 BANDA ACEH - Monika, Nadia; Fitri, Aida; Safiah, Intan (Elementary Education Research, 2023)
This study aims to determine the application of the talking chips model to increase learning motivation in material properties of objects. The method used was Classroom Action Research (CAR). This research was conducted at SD Negeri 27 Banda Aceh with 29 students in class V B as research subjects. Data collection used observation sheets, learning achievement tests and motivational questionnaires. The results of the study in cycle I the average score obtained from student activity was 61.53% with an adequate percentage, and cycle II obtained 86.53% with a very good percentage. The average score obtained from learning outcomes in cycle I was 58.06% with classical mastery of 48.27% and cycle II obtained an average score of 87.58% with a classical value of 86.20%. While the results of learning motivation obtained in cycle I was 58.06% with moderate criteria, and in cycle II the acquisition of student motivation increased to 82.72% with very high criteria. By looking at these results, it can be concluded that the use of the talking chips model can increase students' learning motivation on the material properties of objects in class V SDN 27 Banda Aceh.